On q-Rung Orthopair Fuzzy Subgroups - Asima Razzaque; Abdul Razaq (Journal of Function Spaces)
The q-rung orthopair fuzzy environment is an innovative tool to handle uncertain situations in various decision-making problems. In this work, we characterize the idea of a q-rung orthopair fuzzy subgroup and examine various algebraic attributes of this newly defined notion. We also present q-rung orthopair fuzzy coset and q-rung orthopair fuzzy normal subgroup along with relevant fundamental theorems. Moreover, we introduce the concept of q-rung orthopair fuzzy level subgroup and proved related results. At the end, we explore the consequence of group homomorphism on the q-rung orthopair fuzzy subgroup.